Gel polymer electrolytes for lithium-sulfur batteries. (2018) - Aishova, A.; Mentbayeva, A.; Isakhov, B.; Batyrbekuly, D.; Zhang, Y.; Bakenov, Z.
Abstract: Gel polymer electrolytes (GPE) consisting of a solution of lithium (trifluoromethane)sulfonimide (LiTFSI) dispersed in poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP)/poly(methyl methacrylate) (PMMA)/poly(N-isopropylacrylamide) (PNIPAM) matrix were prepared. Effect of montmorillonite clay mineral additives to stability and electrochemical performance was studied. GPEs exhibited up to 800 wt% electrolyte uptake, high electrochemical and thermal dimensional stability compared to Celgard separator. Li/S cells assembled with S/C composite cathode and PVDF-HFP/PMMA/PNIPAM GPE delivered initial discharge capacities of 1, 300 and 850 mAh g −1 in the first and 15th cycles at 0.1 C, respectively, along with high coulombic efficiency (about 100 %) over 100 cycles. The coulombic efficiency was attributed to the suppression of shuttle effect by the gel polymer electrolyte leading to the higher sulfur utilization in the cell